Orthodontic practices in Australasia: practice activity - Mathew Rachael; Sampson Wayne J.; John Spencer A. (Sciendo, 2005)
Objective: To collect baseline data on practice types and services provided by orthodontists in Australia and New Zealand. Method: A total of 510 questionnaires was sent and 258 were returned. The response rate was 53 per cent.